Analisis Kualitas Lingkungan Aspek Sarana Dan Prasarana RS “X” Kota Depok Tahun 2022 (BERDASARKAN PMK NO 7 TAHUN 2019) - Mulyani, Detty Siti; Sari, Agustina; Hakim, Achmad Lukman (FORUM ILMIAH KESEHATAN, 2023)
Hospital quality is largely determined by two main factors, namely service by hospital staff, as well as facilities and infrastructure. This study aims to analyze the environmental quality of the